ANALISIS PENGARUH KOMPENSASI DAN KECERDASAN EMOSIONAL TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING (Studi Kasus ATR/BPN Kantah Kab. Wonosobo) - Ari Widya Utami; Kusuma Chandra Kirana; Didik Subiyanto (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2022)
The study aims to determine the effect of compensation, emotional intelligence, and job satisfaction on Organizational Citizenship Behavior (OCB) and determine the influence that occurs indirectly on job satisfaction that has a role as a mediator in ATR / BPN Kantah, Wonosobo Regency. Quantitative descriptive research was used by researchers in this study. Employees from ATR / BPN Kantah, Wonosobo Regency became the object of this research. In this study, the questionnaire became a method of data collection used by researchers, with the technique saturated 82 respondents as sampling techniques. Validity and reliability tests are used by researchers to test data quality, with data analysis techniques used, namely classical assumption tests, multiple linear regression tests, hypothesis tests and sobel test. Based on the results of research that has been implemented, it shows that if compensation has a significant positive impact on job satisfaction, emotional intelligence has a significant positive influence on job satisfaction, compensation does not have a significant positive influence on OCB, Emotional intelligence has a significant positive impact on OCB, job satisfaction has a significant positive impact on OCB, job satisfaction can mediate between compensation and OCB, and job satisfaction can mediate for emotional intelligence and OCB.